Problems of special education services for believers in Malang City - Lestari Eko Wahyudi; Bambang Supriyono; Suhartono Winoto (Himpunan Pengembang Kurikulum Indonesia (HIPKIN), 2024)
Over seven years, policy implementation faced challenges, including suboptimal synergy among involved parties, administrative confusion in education, and discrimination against non-religious groups by regional authorities. These challenges perpetuate negative stereotypes and hinder inclusive education access for believers. This research is then directed to analyze the collaborative governance model as a solution to unravel problems that occur in implementing educational services in faith groups. The collaborative governance model aims to elaborate and map the involvement and role of each actor to support the smooth implementation of policies. The principles carried out in it are deliberative, holistic, constructive, and formal, applicable as the basis for implementing inclusive policies. The Soft Systems Methodology (SSM) analysis reveals issues in fulfilling special education services (trust) at the Malang City Education and Culture Office. Problems include partial services, a conservative service acquisition model, and insufficient human resource competence. These findings underscore the need for systemic interventions to ensure inclusive and efficient service delivery. AbstrakSelama tujuh tahun, implementasi kebijakan menghadapi berbagai tantangan termasuk sinergi yang kurang optimal di antara para pihak yang terlibat, kerancuan administrasi pendidikan, dan diskriminasi terhadap kelompok non-religius oleh pemerintah daerah. Tantangan-tantangan ini melanggengkan stereotip negatif dan menghambat akses pendidikan inklusif. Penelitian ini kemudian diarahkan untuk menganalisis model tata kelola kolaboratif sebagai solusi yang ditawarkan untuk mengurai permasalahan yang terjadi dalam proses penyelenggaraan layanan pendidikan pada kelompok. Model collaborative governance bertujuan untuk mengelaborasi dan memetakan keterlibatan dan peran masing-masing aktor untuk mendukung kelancaran implementasi kebijakan. Prinsip-prinsip yang diusung di dalamnya adalah deliberatif, holistik, konstruktif, dan formal yang berguna sebagai dasar dalam mengimplementasikan kebijakan yang inklusif. Analisis Soft Systems Methodology (SSM) mengungkap permasalahan dalam pemenuhan layanan pendidikan khusus (trust) di Dinas Pendidikan dan Kebudayaan Kota Malang. Permasalahan tersebut antara lain layanan yang bersifat parsial, model akuisisi layanan yang konservatif, dan kompetensi sumber daya manusia yang kurang memadai. Temuan ini menggarisbawahi perlunya intervensi sistemik untuk memastikan layanan yang inklusif dan efisien.Kata Kunci: penghayat kepercayaan; tata kelola kolaboratif; pendidikan inklusif; permendikbud nomor 27 tahun 2016